Knowledge Assessment Seven Point Scale - Dyussenbayev, Akhmet (Advances in Social Sciences Research Journal, 2017)
One of the most important components of the educational system is the assessment of knowledge. Nowadays there are an extreme variety of scales and slowness of the process of forming uniform world assessment standards. The model unit of measuring the quantity and quality of knowledge around the world is still missing. Today, different countries of the world use absolutely different scales of knowledge assessment in the following points: 3, 4, 5, 6, 7, 10, 11, 12, 15, 20, 30 and 100 points. There is still no generally accepted objective knowledge assessment scale across the globe to be most convenient for the examiner. A universal system of objective assessment of knowledge of pupils, students and teachers is extremely necessary in the XXI century. This is an obligatory condition for the high-quality education and upbringing of the younger generation.